Oxidative Stress and Ischemia/Reperfusion Injury in Kidney Transplantation: Focus on Ferroptosis, Mitophagy and New Antioxidants - Simona Granata; Valentina Votrico; Federica Spadaccino; Valeria Catalano; Giuseppe Stefano Netti; Elena Ranieri; Giovanni Stallone; Gianluigi Zaza (MDPI AG, 2022)
Although there has been technical and pharmacological progress in kidney transplant medicine, some patients may experience acute post-transplant complications. Among the mechanisms involved in these conditions, ischemia/reperfusion (I/R) injury may have a primary pathophysiological role since it is one of the leading causes of delayed graft function (DGF), a slow recovery of the renal function with the need for dialysis (generally during the first week after transplantation). DGF has a significant social and economic impact as it is associated with prolonged hospitalization and the development of severe complications (including acute rejection). During I/R injury, oxidative stress plays a major role activating several pathways including ferroptosis, an iron-driven cell death characterized by iron accumulation and excessive lipid peroxidation, and mitophagy, a selective degradation of damaged mitochondria by autophagy. Ferroptosis may contribute to the renal damage, while mitophagy can have a protective role by reducing the release of reactive oxygen species from dysfunctional mitochondria. Deep comprehension of both pathways may offer the possibility of identifying new early diagnostic noninvasive biomarkers of DGF and introducing new clinically employable pharmacological strategies. In this review we summarize all relevant knowledge in this field and discuss current antioxidant pharmacological strategies that could represent, in the next future, potential treatments for I/R injury.